(3cJGH aj GdJaSjQs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CfRd GdaQbGf TaGA deG aj GdUOhQ hQMeI ddeDefjf CeG HYO CYde Cf GdJaSjQ ef CLd GdeWGdH hCSfGgG bO hbY Pgfj GdYdjd YfO JdGhI cdGe Gddg GdLdjd Cf CLeY ef JaGSjQ GdeJbOejf eNJUQG jYjf GdbGQA Ydi eYfi QhGjI CHj MaU Hf SdjeGf (B( (3cPG (B) (3heHjfG BjGJ GdCMcGe Ydi ePgH CHj MfjaI GdfYeGfs
(3BNQgG (B:s
(3ShQI GdfGS hgS ecjI hgj SHY hbjd SJ BjGJ ef TQ GdhShGS Cj GdehShS Sej HaYdg eHGdZI , GdNfGS (B: (3GdPj YGOJg Cf jNfS Cj jJCNQ EPG PcQ Gddg, GdPj jhShS aj UOhQ GdfGS (B: (3aj bdhHge s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJ hMhGTj HGdaGQSjI hGdYQHjIs
Keywords: (3GdJaSjQ hYdhe GdbQBfs